2018
DOI: 10.3390/su10082927
|View full text |Cite
|
Sign up to set email alerts
|

Online and Offline Communities in the Sharing Economy

Abstract: Abstract:The online community is crucial to sharing economy platforms because without it, no transactions can take place. Online communities have been studied extensively, but so far, little attention has been paid to how they link to different offline communities, such as geographic (e.g., neighborhoods) and relational communities (e.g., friends and colleagues). In this study, we address this gap by examining the importance of communities to the users and the entrepreneurs of the goods-sharing platform Ecomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Platforms use smartphone apps , web-based platforms and other third-party applications to mediate sharing between users ( Aboulamer, 2018 ; Gonzalez-Padron, 2017 ). The initial attribute of openness was changed to intellectual property , as several authors discuss open source characteristics of business models in the sharing economy ( Lobbers et al., 2017 ; Muñoz and Cohen, 2018 ; Spulber, 2019 ; Vaskelainen and Piscicelli, 2018 ). Other authors discussed intellectual property rights ( Fraga-Lamas and Fernández-Caramés, 2019 ; Hamalainen and Karjalainen, 2017 ; Hou, 2018 ), which seemed to be a better fit in describing both the type of resources used by platforms and the openness of platforms to share these resources.…”
Section: Sharing Economy Business Modelling Toolmentioning
confidence: 99%
“…Platforms use smartphone apps , web-based platforms and other third-party applications to mediate sharing between users ( Aboulamer, 2018 ; Gonzalez-Padron, 2017 ). The initial attribute of openness was changed to intellectual property , as several authors discuss open source characteristics of business models in the sharing economy ( Lobbers et al., 2017 ; Muñoz and Cohen, 2018 ; Spulber, 2019 ; Vaskelainen and Piscicelli, 2018 ). Other authors discussed intellectual property rights ( Fraga-Lamas and Fernández-Caramés, 2019 ; Hamalainen and Karjalainen, 2017 ; Hou, 2018 ), which seemed to be a better fit in describing both the type of resources used by platforms and the openness of platforms to share these resources.…”
Section: Sharing Economy Business Modelling Toolmentioning
confidence: 99%
“…Cooperatives then, would most likely emerge from local communities that use a platform to serve local consumers, as in most gig economy and sharing economy markets. In such context, an online community of providers can easily interact offline as well (Reischauer & Mair, 2018;Vaskelainen & Piscicelli, 2018), thus leveraging the physical proximity of providers operating in local markets. In particular cases, the membership of a platform co-op may be tight formally to a membership of a (national) professional organization as well, or otherwise informally to professional values and identities.…”
Section: Community Logicmentioning
confidence: 99%
“…Albinsson and Perera [11] believed that individuals involved in collaborative consumption have established communities through shared activities. Vaskelainen and Piscicelli [31] found that offline communities are as important as online communities. In C2C-style collaborative consumption, direct human-to-human interaction and experience in sharing goods create and maintain social relationships with others, while, in B2C-style collaborative consumption, although there is no direct relationship between users, they may still think that they are part of a community that uses a certain common product, and this sense of community will make them feel psychologically fulfilled, happy and satisfied, thus increasing their intention to participate.…”
Section: Intrinsic Motivationmentioning
confidence: 99%